Interaction of water stress and aluminum toxicity in pigeon pea cultivated in hydroponics - Marin, Adão (2008)
The objective of this work was to evaluate the interaction effect of water stress and aluminum toxicity on the initial growth and free proline contents in two cultivars of pigeon pea, IAPAR 43-Aratãand IAC Fava Larga, cultivated in hydroponics. The seedlings were submitted to stresses in nutritive solution (pH 3.8), osmotic potentials 0, -0.004, -0.006, -0.008 and -0.010 MPa, with 0, 0.25, 0.50, 0.75and 1 mmol dm-3 Al3+. The experiment was carried out in a plant growth room, under a luminary unit of average irradiance 190 μmol m-2 s-1, 12-hour photoperiod and 25+1ºC temperature. A completely randomizedexperimental design was used in factorial arrangement 2x5x5 (two pigeon pea cultivars, fi ve osmotic potential and fi ve levels), with four replicates. Data were submitted to analyses of polynomial regression, cluster and main components. Water stress causes growth reduction of pigeon pea aerial part, whereas aluminum toxicitycauses radicular growth reduction. There was increase of free proline contents in the two cultivars under water stress, and only in IAC Fava Larga under aluminum toxicity. Multivariate analysis showed high correlation in growth and accumulation of proline for cultivar IAC Fava Larga, evidencing probable tolerance to associated stresses.